2010
DOI: 10.1111/j.1365-3156.2010.02656.x
|View full text |Cite
|
Sign up to set email alerts
|

Subtype prevalence, plasmid profiles and growing fluoroquinolone resistance in Shigella from Kolkata, India (2001-2007): a hospital-based study

Abstract: Summaryobjectives Shigellosis is a major public health problem, and increasing antimicrobial resistance has complicated its treatment. We report isolation frequency, plasmid profiles and antimicrobial resistance of Shigella subtypes in Kolkata, India, from a prospective hospital-based study.methods Fresh stool or rectal swabs were collected from children (<5 years) attending the Diarrhea Treatment Unit of a governmental paediatric referral hospital in Kolkata. Samples were processed following standard methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 27 publications
1
24
1
Order By: Relevance
“…In uni-variate analysis, we further observed that the infection with Shigella sonnei was significantly associated with encephalopathy, although many previous studies have reported no association between the infecting species of Shigella with encephalopathy [10,11,44]. Our observed association might represent the rising trend and increasing virulence of Shigella sonnei [1,45,46]. We also observed Shigella sonnei as the second most common species of Shigella among our study population [1], which might represent the improvement of overall nutritional and socioeconomic status.…”
Section: Discussionmentioning
confidence: 52%
“…In uni-variate analysis, we further observed that the infection with Shigella sonnei was significantly associated with encephalopathy, although many previous studies have reported no association between the infecting species of Shigella with encephalopathy [10,11,44]. Our observed association might represent the rising trend and increasing virulence of Shigella sonnei [1,45,46]. We also observed Shigella sonnei as the second most common species of Shigella among our study population [1], which might represent the improvement of overall nutritional and socioeconomic status.…”
Section: Discussionmentioning
confidence: 52%
“…sonnei to grow successfully within Acanthamoeba but may also be due to a potential, but as yet unproven, ability to acquire and/or maintain a wider array of antimicrobial resistance genes. Indeed, it has been speculated that the plasmid composition and resistance profiles may differ between the Shigella species isolated from contemporaneous patient populations in the same locations (Fig 2) [15,66–71]. Although S .…”
Section: Does Shigella Sonnei Have a Competitive Advantage?mentioning
confidence: 99%
“…The available information on foodborne disease outbreak investigation from 1980 to 2009 indicated that a total of 37 outbreaks affected 3,485 persons (8). In 1984In -1985 dysentery outbreaks were reported due to infection with Shigella dysenteriae type 1 (9). Although Shigella dysenteriae and Shigella flexneri are the predominant species in tropical countries, foodborne outbreaks due to Shigella sonnei are also being reported in countries like India (9).…”
Section: Introductionmentioning
confidence: 99%
“…Although Shigella dysenteriae and Shigella flexneri are the predominant species in tropical countries, foodborne outbreaks due to Shigella sonnei are also being reported in countries like India (9). In 2009-2010, 2 foodborne outbreaks caused by S. sonnei were reported in India (9).…”
Section: Introductionmentioning
confidence: 99%